MENEROPONG TIPOLOGI BAHASA-BAHASA DI PAPUA: SUATU TINJUAN SINGKAT - Yusuf Willem Sawaki (SCOPUS ID: 18635502400) (Linguistik Indonesia, 2018)
Tanah Papua, both the Indonesia provinces of Papua and West Papua, is the most diverse linguistic region that has the highest number of indigenous languages in Indonesia. Out of 760s languages in Indonesia, Tanah Papua has about 270s languages. The diversity of languages are not only about the number of languages but also about the linguistic features. Languages is Tanah Papua are divided into two major groups, which are Austronesian and non-Austronesian (known as Papuan) languages. Both major linguistic groups contribute diverse linguistic features ranging from phonological system, word, phrase, clause and sentence structures, as well as diversity of semantic and pragmatic structures. The linguistic diversity is also determined by a contact language history in the region that has been occurred for centuries, especially in the regions of Jayapura and the Bird’s Head of New Guinea. Although the region is linguistically rich, not many linguistic reseach has been doing in the region. We therefore do not have a comprehensive understanding about languages in Papua yet. The purpose of this paper is to give a brief description about grammatical features of languages in Tanah Papua.